Demonstrating the Clinical Impact of Continuous Glucose Monitoring Within an Integrated Healthcare Delivery System. (March 2022) - Isaacson, Brad; Kaufusi, Stephanie; Sorensen, Jeff; Joy, Elizabeth; Jones, Christopher; Ingram, Valerie; Mark, Nickolas; Phillips, Mike; Briesacher, Mark
Background: Approximately 30 million Americans currently suffer from diabetes, and nearly 55 million people will be impacted by 2030. Continuous glucose monitoring (CGM) systems help patients manage their care with real-time data. Although approximately 95% of those with diabetes suffer from type 2, few studies have measured CGM's clinical impact for this segment within an integrated healthcare system. Methods: A parallel randomized, multisite prospective trial was conducted using a new CGM device (Dexcom G6) compared to a standard of care finger stick glucometer (FSG) (Contour Next One). All participants received usual care in primary care clinics for six consecutive months while using these devices. Data were collected via electronic medical records, device outputs, exit surveys, and insurance company (SelectHealth) claims in accordance with institutional review board approval. Results: Ninety-nine patients were randomized for analysis ( n  = 50 CGM and n  = 49 FSG). CGM patients significantly decreased hemoglobin A1c ( p  = .001), total visits ( p  = .009), emergency department encounters ( p  = .018), and labs ordered ( p  = .001). Among SelectHealth non-Medicare Advantage patients, per member per month savings were $417 for CGM compared to FSG, but $9 more for Medicare Advantage. Seventy percent of CGM users reported that the technology helped them better understand daily activity and diet compared to only 16% for FSG. Discussion: Participants using CGM devices had meaningful improvements in clinical outcomes, costs, and self-reported measures compared to the FSG group. Although a larger study is necessary to confirm these results, CGM devices appear to improve patient outcomes while making treatment more affordable.